Resistance and Response of Steel and Steel-Concrete Composite Structures in Progressive Collapse Assessment - Kuhlmann, Ulrike; Rölle, Lars; Izzuddin, Bassam A.; Pereira, Miguel F. (Structural engineering international : journal of the International Association for Bridge and Structural Engineering (IABSE), 2012)
Within this article particularities concerning the handling of material characteristics of steel-concrete composite for progressive collapse assessment are discussed. How to influence the redundancy of the global structure not only by high material strength but also by highly ductile material behaviour is highlighted. Beside the material characteristics strength and ductility further important properties under the aspect of robustness, like over-strength effects, strain rate sensitivity and absorption capacity are within the scope of the paper. For ultimate limit state and service limit state analysis under basic design conditions the proof of all relevant structural elements as separate members is state-of-the-art in most of the codes and standards and is in line with the safety concept. So, most practical engineers are only familiar with considering basic design criteria for planning. Going beyond the "normal loading conditions" additional considerations are necessary to ensure structural safety for abnormal loading and for mitigating progressive failure when local damage occurs. Therefore it is fundamental for the structural engineer to be aware of modelling the actual structural response in a correct manner. Besides the knowledge of the modelling technique itself, information about the actual material behaviour is of high importance. But in nearly all current codes only nominal material models are available. So it is hardly possible for the practical engineer to get expected material properties of the relevant material characteristic as input for progressive collapse assessment. Within this article detailed information about the actual behaviour of steel-concrete composite will be provided.